A Semi‐artificial Photoelectrochemical Tandem Leaf with a CO2‐to‐Formate Efficiency Approaching 1 %. Issue 50 (11th October 2021) - Edwardes Moore, Esther; Andrei, Virgil; Oliveira, Ana Rita; Coito, Ana Margarida; Pereira, Inês A. C.; Reisner, Erwin
Abstract: Semi‐artificial photoelectrochemistry can combine state‐of‐the‐art photovoltaic light‐absorbers with enzymes evolved for selective fuel‐forming reactions such as CO2 reduction, but the overall performance of such hybrid systems has been limited to date. Here, the electrolyte constituents were first tuned to establish an optimal local environment for a W‐formate dehydrogenase to perform electrocatalysis. The CO2 reductase was then interfaced with a triple cation lead mixed‐halide perovskite through a hierarchically structured porous TiO2 scaffold to produce an integrated photocathode achieving a photocurrent density of −5 mA cm −2 at 0.4 V vs. the reversible hydrogen electrode during simulated solar light irradiation. Finally, the combination with a water‐oxidizing BiVO4 photoanode produced a bias‐free integrated biophotoelectrochemical tandem device (semi‐artificial leaf) with a solar CO2 ‐to‐formate energy conversion efficiency of 0.8 %. Abstract : Formate dehydrogenase was interfaced with a perovskite to produce a photocathode that benefits from an optimized local enzyme environment via the electrolyte solution and achieves an unprecedented current density. Combination with a BiVO4 water oxidation photoanode gave a bias‐free biophotoelectrochemical tandem leaf with a CO2 ‐to‐formate conversion efficiency of 0.8 %.